A very rare case report of giant calculus in bulbar urethra - Garg, Navdeep; Batra, Ravi; Sharma, Kamal (International Surgery Journal, 2016)
Urethral stones in adults are very rare and developed usually with urethral stricture or diverticulum. This is case report of 45 years old man who presented with a large urethral calculus in bulbar urethra resulting from an anterior urethral stricture. The patient presented with dribbling of urine from an opening in scrotal region for 3 months. On examination hard dull aching mass of size 3X2cm was palpable from bulbar urethra to anterior perineum. The calculus was removed by external urethrotomy with two layer closure of urethra.